Perancangan Sistem Informasi Pemesanan Menu Berbasis Web (Studi Kasus: Warunk Endess) - Minda Mora Purba; Siti Nurhaliza (Fakultas Ilmu Komputer dan Desain - Unsurya, 2023)
Warunk Endess is a drinks shop with a choice of food and drinks in various flavors. However the ordering system at Warunk Endess only applies the usual ordering menu, like a customer who has to come to Warunk Endess, queue to place an order, choose a table and then wait for the waiter come to take orders. The problem that is often faced is too much queue of customers due to ordering food and beverage menus only through one place at Warunk Endess. So that makes customer service worse. To support the convenience of the ordering process at Warunk Endess, a system is designed that makes it easier to order without queuing. This research uses the methods of data collection including literature study, interviews and observations. The system development method uses the System Development Life Cycle (Waterfall) method, the programming language used is PHP and the MySQL database. This research produces a menu ordering website which can provide convenience to customers in the process of ordering and selling food and beverages at Warunk Endess.